Phytochemicals with antifungal properties: Cure from nature - Elgharbawy, Amal A.M.; Samsudin, Nurhusna; Benbelgacem, Farah Fadwa; Hashim, Yumi Zuhanis Has-Yun; Salleh, Hamzah Mohd.; Santhanam, Jacinta (2020)
Aims: The exploration of natural products with innovative uses is dynamic and expanding rapidly. Medicinal plants have fascinated many researchers that subsequently lead to research publications highlighting plant extracts with wide range of secondary metabolites such as flavonoids, alkaloids, glycosides, quinones, terpenoids, tannins and saponins that exhibit antimicrobial activities and disease control. The concentration of these bioactive compounds in each plant species varies based on the pathosystem and environmental conditions. This study aims to uncover the various types of phytochemicals with antifungal properties.